2021
DOI: 10.1146/annurev-cancerbio-060920-084910
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Immunotherapy and the Nectin Family

Abstract: It is increasingly clear that the nectin family and its immunoreceptors shape the immune response to cancer through several pathways. Yet, even as antibodies against TIGIT, CD96, and CD112R advance into clinical development, biological and therapeutic questions remain unanswered. Here, we review recent progress, prospects, and challenges to understanding and tapping this family in cancer immunotherapy. Expected final online publication date for the Annual Review of Cancer Biology, Volume 5 is March 4, 2021. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 137 publications
3
9
0
Order By: Relevance
“…For another example, we also identified the involvement of NECTIN pathway during the interaction between the activated macrophages (source) and TRM CD8 T cells (target). This is consistent with the previous report that NECTIN (CD155) expressed on tumor-infiltrating macrophages could be immunosuppressive when interacting with surface receptors on CD8+ T cells in the lung cancer TME 21,22 . Protein Gene…”
Section: Deepmaps Accurately Identify Cell Types In Pbmc and Lung Tumor Immune Citeseq Datasupporting
confidence: 93%
See 1 more Smart Citation
“…For another example, we also identified the involvement of NECTIN pathway during the interaction between the activated macrophages (source) and TRM CD8 T cells (target). This is consistent with the previous report that NECTIN (CD155) expressed on tumor-infiltrating macrophages could be immunosuppressive when interacting with surface receptors on CD8+ T cells in the lung cancer TME 21,22 . Protein Gene…”
Section: Deepmaps Accurately Identify Cell Types In Pbmc and Lung Tumor Immune Citeseq Datasupporting
confidence: 93%
“…Previous studies have shown that ALCAM on antigenpresenting DCs interact with CD6 on the T cell surface and contribute to T cell activation and proliferation [18][19][20] . As another example, we identified the involvement of the NECTIN-TIGIT signaling pathway during the interaction between the TAM (source) and TRM CD8 + T cells (target), which is supported with a previous report that NECTIN (CD155) expressed on TAM could be immunosuppressive when interacting with surface receptors, TIGIT, on CD8 + T cells in the lung cancer TME 21,22 . Protein Gene…”
Section: Deepmaps Accurately Identify Cell Types and Infer Cell-cell Communication In Pbmc And Lung Tumor Immune Cite-seq Datasupporting
confidence: 89%
“…The T Cell Immunoreceptor With Ig and ITIM Domains (TIGIT) family of receptors and ligands (hereafter, receptors/ligands) functions as an immune checkpoint to limit immune responses in model systems of viral infections and cancer (12)(13)(14). TIGIT is expressed on T cells and natural killer (NK) cells (15).…”
Section: Resultsmentioning
confidence: 99%
“…Nectin family members are expressed by different cell types within the TME [56]. Although primarily regulators of cell adhesion, migration, and proliferation, several nectins have been shown to modulate immune responses in the TME via interactions with the T cell activating receptor CD226 (DNAM-1), or with the inhibitory receptors T cell immunoglobulin and ITIM domain (TIGIT), CD96 and CD112R (PVRIG) [57][58][59][60][61][62]. While the role for CD96 in tumor immunity is controversially discussed, TIGIT is a well-established immune checkpoint [63].…”
Section: Immunosuppressive Molecules Expressed On the Cell Surface Of...mentioning
confidence: 99%